The The Great Fire of London as a Memory Site (Lieu de Mémoire) - Tomczak, Anna Maria (Załącznik Kulturoznawczy, 2019)
The author approaches the Great Fire of London of 1666 as a memory site, using Pierre Nora’s concept to analyse various forms and acts of remembrance of this historic event. Special attention is paid to John Dryden’s poem Annus Mirabilis, fragments of Samuel Pepys’s Diary, the architectural Monument of the Great Fire in the City of London, and the celebrations of the 350th anniversary with its spectacular London’s Burning festival. Nora’s idea of lieu de mémoire, when used as a conceptual tool, makes it possible to link collective memory and identity, not through a linear historic narration of a society’s past but through specific individual events and their symbolic impact. As a social construct, collective memory is an important constitutive element of national identity. The memory of the Great Fire – in its material, symbolic and functional aspects – fosters cultural identity of the British and the feeling of belonging.